INTO THE MAINSTREAM LIFE OR DID I GROW UP ABSURD? - Beane, E. F. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1974)
School is a Sheltered Enviromnent. Of course it is not without its brutal and abusive aspects, and there is more than enough literature on that score written in the last decade to attest to that. The point, however, I wish to make is that school shelters an individual in the most negative of fashions by not giving young persons adequate preparation for life, often muddling their minds up in the process by giving them a mistaken idea of the priorities of life by means of which they can manoeuver more effectively into and through this Brave New World of ours. This realization comes upon a body quite cataclysmically and, I feel, far too often catastrophically, when the young person makes his departure out the quasi-womb precincts of the school environment into what is called "The World" and what I, in this account, shall refer to as "Mainstream Life."